2007
DOI: 10.1177/1091142106290453
|View full text |Cite
|
Sign up to set email alerts
|

Public Observability of Decisions and Voluntary Contributions in a Multiperiod Context

Abstract: The authors conduct an experiment to explore whether contributions to a public good increase when public observation of contribution decisions is possible and whether any such increase is durable and transferable. Rege and Telle (2004) find that in one-shot games, public observation of all individuals' contribution decisions leads to higher contributions than would occur in the absence of such observation. In this study, the authors argue that public observation is ineffective in increasing contributions in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 11 publications
(36 reference statements)
2
31
1
Order By: Relevance
“…On the one hand, disclosing the income-relevant contribution of each participant means that our paper is in line with previous literature that has studied the effect of disclosure on contributions to a public good which ex-ante facilitates comparison with other papers that have studied the issue like Rege and Telle (2004) and Noussair and Tucker (2007). On the other hand, it is difficult to know if, and if so, how, disclosing their income-relevant contribution rather than their strategy affects subjects' behavior.…”
Section: Experimental Designsupporting
confidence: 62%
See 3 more Smart Citations
“…On the one hand, disclosing the income-relevant contribution of each participant means that our paper is in line with previous literature that has studied the effect of disclosure on contributions to a public good which ex-ante facilitates comparison with other papers that have studied the issue like Rege and Telle (2004) and Noussair and Tucker (2007). On the other hand, it is difficult to know if, and if so, how, disclosing their income-relevant contribution rather than their strategy affects subjects' behavior.…”
Section: Experimental Designsupporting
confidence: 62%
“…It should however be noted that previous findings on the effect of introducing disclosure on contributions are mixed (e.g., Rege and Telle, 2004;Noussair and Tucker, 2007). The small positive effect from disclosure may indicate either that the image motivation to increase contribution level when subject to disclosure is small or the net effect of image and intrinsic motivations is small.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…This can be characterized as "conditional cooperation". However, Noussair and Tucker (2007), employing the same design as Rege and Telle (2004), and extending their one-shot game to a multiperiod game, found that public disclosure of own contribution had no effect on subsequent contributions in the public good experiment. Also, Martisson et al (2013) did not find any significant difference in unconditional contributions between the no-disclosure and disclosure treatments.…”
Section: Introductionmentioning
confidence: 99%